Analisa Pengaruh Kepribadian, Sikap, Dan Disiplin Kerja Terhadap Kinerja Aparatur Desa Sekecamatan Musuk - Wulandari, Heni; , Nur Achmad, SE., M.Si (2017)
This study aims to determine the influence of personality, attitudes, and work discipline on Performance. The sample in this study were employees who worked in the village officials sekecapamatan enemy of totaling 30 respondents. The sampling technique in this research is purposive sampling. Data analysis methods digunakana dalah normality test, multicollinearity, heteroskedasitas test and test multiple linear regression analysis with t-test, F, and the coefficient of determination (R2). In this study the data meet for a normal distribution. Hypothesis tests showed that the personality and the Discipline of work has a significant impact with the t respectively 2.335 and 2.215 whereas attitudinal variables do not have significant influence is evidenced by the t value of 0.876. At f test showed that together the variables of personality, attitude, and discipline significant influence on employee performance. The coefficient of determination (R2) was 66.6% Keywords: personality, attitude, work discipline, and employee performance